(untitled) (Scientific journal of the Fergana State University, 2026)
This article analyzes the social and political factors that are manifested in the process of forming an inclusive society in Uzbekistan, as well as from a philosophical point of view, based on foreign scientific research. It is shown that the principles of human dignity, social justice and equal opportunities constitute the ideological basis of modern changes. The transformation of the mahalla institution, the inclusive education system, youth policy and civic activism are interpreted as the foundations of an inclusive society.